A man with worsening gastrointestinal and neurologic symptoms. Issue 8 (August 2016) - Irving, David
Abstract : ABSTRACT: A Coast Guardsman deployed to a remote island in the Bahamas contacted his primary care office about worsening gastrointestinal and neurologic complaints. This article describes the telemedicine consultation to determine the cause of his symptoms, whether he needed emergency evacuation, and how treatment was handled.